Treatment of industrial dye effluent: a pre-pilot plant scale study based on circular liquid–liquid extraction using pseudoprotic ionic liquids - Sachind Prabha Padinhattath; Jegan Govindaraj; Ramesh L. Gardas (Green Chemistry Letters and Reviews)
The hazardous chemicals discharged from various dyeing industries adversely impact human health and the environment. Therefore, it is essential to treat wastewater containing dyes with technology that outperforms conventional methods. In the current study, liquid–liquid extraction (LLE) based on pseudoprotic ionic liquids (PPILs) was employed as an efficient tool to remove anionic dyes from simulated and real dye effluent. PPIL derived from trioctylamine and octanoic acid was used for the extraction studies. Initially, simulated dye samples were prepared using different anionic dyes, namely alizarin yellow, rose Bengal, and methyl orange, identical to the real industrial dye effluent composition, and LLE studies were carried out. After a series of screenings, the essential experimental parameters required for deploying a pre-pilot plant scale study have been optimized systematically. After successful optimization, similar experimental parameters were deployed for the removal of dyes from the industrial dye effluent collected from Angeripalayam common effluent treatment plant limited (ACETP), Tirupur, Tamil Nadu, India. While most optimized reaction conditions remained unaltered, adjustments were made to some, such as pH, to suit practical scenarios. Moreover, the dyes were back-extracted with dilute diethylamine and the regenerated extractant was reused in subsequent LLE cycles.